INNOVATIVE MANAGEMENT TECHNOLOGIES IN ENSURING THE ECONOMIC SECURITY OF ENTERPRISES AND DEVELOPING THEIR POTENTIAL (Development Service Industry Management, 2025)
The theoretical, methodological and applied aspects of the selection and application of risk reduction management technologies, ensuring the economic security of enterprises and developing their potential in modern turbulent business conditions are summarized. Attention is focused on the need and features of the application of innovative management technologies. It is proven that the effectiveness of managing the economic security of an enterprise significantly depends on the correct prediction of the consequences of a risk situation and assessing the level of risk, and a flowchart of the process of managing the economic security of an enterprise is proposed.It is concluded that in the practice of European management, three basic groups of technologies in management are noted: technologies for planning management decisions, technologies for implementing and technologies for changing the structure of the enterprise, and in practice, Ukrainian entrepreneurs most often use the grouping of management technologies according to their functional purpose: resource management, personnel management, business process management, strategic management, etc. At the same time, there is a shift in emphasis from the production to the market management system, from traditional management methods to innovative methods of managing technological development, the formation of information systems and databases on entrepreneurial activity, the use of artificial intelligence and cloud technologies, which are primarily aimed at reducing market risks, ensuring economic security and developing the potential of the enterprise.
Keywords: management technologies; enterprise management; economic security; risks; digital tools; cloud technologies; enterprise potential; innovation; development